DEVELOPMENT OF TOURISM ACTIVITY AND MARKETING COMMUNICATION OF PERFORMING ARTS AND MARTIAL ARTS TO BE EXPERIENTIAL TOURISM - Chamnian, Methawee; Chamnian, Korrakot; Kaewsanit, Thatsanawadi; Suwantip, Natthawut; Kaewsanit, Mathee (Dusit Thani College Journal, 2021)
In each region and each locality of Thailand has arts and culture that is unique which depends on the context, spatial environment and history. People in each locality accumulate wisdom, including ideas, belief, wisdom, tradition, culture, objects, products, etc. The unique characteristic of each locality can be developed and communicated for tourists to experience. The authors present the performing arts and martial arts as case studies to develop as tourism activity and use marketing communication as experience tourism. To develop tourism activity should come from the identity of that community, either existing activity or newly created activity. For using marketing communication with tourists, the community should communicate the story of arts and culture that can create experience or benefit for tourists. They will receive from learning through tourism activities and including links to local attractions through using various marketing communication tools to support altogether; in particularly online marketing communication tool.